A multicentre clinical evaluation of paediatric cochlear implant users upgrading to the Nucleus® 6 system. (April 2016) - Plasmans, Anke; Rushbrooke, Emma; Moran, Michelle; Spence, Claire; Theuwis, Leen; Zarowski, Andrzej; Offeciers, Erwin; Atkinson, Beth; McGovern, Jane; Dornan, Dimity; Leigh, Jaime; Kaicer, Arielle; et al.
Abstract: Objectives: The aim of this study was to investigate whether experienced paediatric cochlear implant users could show benefits to speech perception outcomes from the introduction of noise reduction and automated scene classification technologies as implemented in the Nucleus ® 6 sound processor. Previous research with adult cochlear implant users had shown significant improvements in speech intelligibility for listening in noisy conditions and good user acceptance for upgrading to the Nucleus 6 processor. In adults, these improvements for listening in noise were primarily attributed to the use of a range of new input processing technologies including noise reduction, as well as introduction of automatic scene classification technology. Methods: Experienced paediatric cochlear implant users ( n = 25) were recruited from four clinics located in three countries. Research participants were evaluated on three occasions, an initial session using their Nucleus 5 sound processor; a second session in which participants used the Nucleus 6 processor programmed with the same technologies as were used in their Nucleus 5 sound processor; and a final session in which participants used the Nucleus 6 processor programmed with the default technologies including automatic scene classification (SCAN) which automatically selects the microphone directionality, noise reduction (SNR-NR), and wind noise reduction (WNR) technologies. Prior to both the second and third evaluations, research participants had approximately two weeks take-home experience with the new system. Speech perception performances on monosyllabic word tests presented in quiet and in noise, and a sentence test presented in noise, were compared across the three processor conditions. Acceptance of the Nucleus 6 default settings was assessed in a final session. Results: No group mean difference in performance was found for monosyllabic words in quiet. A significant improvement in speech perception was found for both monosyllabic words and sentences in noise with the default Nucleus 6 program condition as compared with the Nucleus 5 condition. No acceptance issues were noted for any of the children. Conclusions: Experienced paediatric cochlear implant users showed a significant improvement in speech perception in listening in noise when upgraded to the Nucleus 6 sound processor primarily due to the introduction of a noise reduction technology, and all children accepted the default program. These findings suggest that school-aged children may benefit from upgrading to the Nucleus 6 sound processor using the default program.